(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Formulation of the problem. Increasing sunflower productivity largely depends on the efficiency of the photosynthetic apparatus, particularly the leaf area, which determines the intensity of assimilatory processes. At the same time, its formation is governed by both genotypic characteristics and agronomic practices, among which pre-sowing seed treatment with growth stimulants and micronutrients plays an important role. The insufficient study of their effects on different sunflower lines under the conditions of the Eastern Forest-Steppe of Ukraine determines the relevance of this research. Purpose. To determine the peculiarities of the formation of the photosynthetic surface of sunflower lines depending on different variants of pre-sowing seed treatment and to assess their impact on yield. Methods. Field experiments were conducted during 2022–2024 on typical medium-humus slightly leached chernozem soils. The objects of the study were sunflower lines Sх17A, Sх51A, and Sх808A. The experimental design included various variants of pre-sowing seed treatment using seed dressers, growth stimulants, and micronutrients. Leaf area and yield were measured, and analysis of variance, correlation, and regression analyses were applied. Results. It was established that the photosynthetic surface significantly varied depending on genotype and seed treatment variant. The highest values were observed in line Sх808A, while the lowest were recorded in Sх51A. The application of growth stimulants and micronutrients generally increased leaf area, with the most effective treatments involving Nertus Plantapeg, Nertus Start, and Raikat Start. According to the analysis of variance, the contribution of genotype was 77%, year conditions – 8%, and seed treatment – 3%. A strong positive correlation between leaf area and yield was revealed (r = 0.920; R² = 0.846). The greatest yield increase was obtained in treatments with Nertus Plantapeg and AKM. Conclusions. The formation of the photosynthetic surface of sunflower lines is mainly determined by the genotype, which has a dominant effect, while pre-sowing seed treatment and year conditions have a smaller but statistically significant effect. The regression coefficient shows that an increase in leaf surface area by 1 thousand m²/ha is accompanied by an increase in yield by an average of 0.055 t/ha.